The Indirect Effect of Peritraumatic Dissociation on the Relationship Between Childhood Maltreatment and Schizotypy - Blose, Brittany A. (Journal of interpersonal violence, 2023)
Schizotypy is a multidimensional personality construct that is understood as a vulnerability for schizophrenia, often manifesting as more subtle and attenuated symptoms, referred to as schizotypic psychopathology. It has many well-established environmental risk factors, including experiencing childhood maltreatment (CM), but the intermediary mechanisms that relate CM to schizotypic psychopathology are unclear. Prior studies have demonstrated that trait dissociation may indirectly affect the relationship between CM and schizotypic psychopathology. However, less is known about the importance of peritraumatic dissociative experiences during CM and how it relates to schizotypic symptom manifestations in young adulthood. Therefore, the present study explored the independent contributions of peritraumatic and trait dissociation in the relationship between CM and schizotypy. Participants (N = 346) were undergraduate students who completed online self-report measures on CM, trait dissociation, peritraumatic dissociation experienced during CM, and schizotypic symptoms. The indirect effect of peritraumatic dissociation and trait dissociation on the relationship between CM and schizotypy was examined using mediational analyses. Correlational analyses revealed significant associations between self-reported CM, schizotypy, trait dissociation, and peritraumatic dissociation. In addition, mediational analyses indicated a significant indirect effect of peritraumatic dissociation (β = .06, 95% confidence interval (CI) [0.01, 0.12]), but not trait dissociation (β = .05, 95% CI [−0.02, 0.12]), on CM and schizotypy. These results highlight peritraumatic dissociation as an important mechanism driving the expression of schizotypic symptoms among individuals with a history of CM. Understanding how trauma sequelae lead to schizotypic psychopathology may be crucial in assessing and treating individuals with maltreatment histories or those on the psychosis spectrum.